Organizational Silence: Dimensions, Determinants, and Impact on Management - an Analytical Study - Slimane Tichtich, Mohamed Lamine; Amira, Khaiat (Journal of Vasyl Stefanyk Precarpathian National University, 2024)
Organizational silence is a significant problem that hinders efficient communication, diminishes employee involvement, and has a detrimental impact on overall organizational performance. This study examines the different aspects of organizational silence, including defensive, acquiescent, and social quiet, and how each of these affects organizational outcomes in unique ways. The study examines how various human elements, such as age, gender, and educational qualifications, as well as organizational aspects, such as culture, knowledge management, and internal entrepreneurial settings, affect the occurrence of silence within businesses. Through an extensive examination of relevant literature and careful analysis of existing empirical studies, the research affirms that organizational silence has a substantial negative impact on creativity, work satisfaction, and productivity. The study also emphasizes the harmful consequences of an opaque, fear-driven company culture in promoting quiet. On the other hand, research has demonstrated that an organizational atmosphere that is supportive and transparent can effectively decrease instances of silence among employees. This, in turn, leads to increased employee participation and facilitates the development of innovative ideas. The results have practical consequences for leaders in organizations and politicians, highlighting the importance of developing transparent channels of communication and a culture that promotes inclusivity, where employees feel comfortable expressing their thoughts without any negative consequences. Consequently, this is essential for fostering innovation, enhancing decision-making procedures, and attaining long-term strategic objectives. The study provides useful insights for businesses aiming to comprehend and alleviate the adverse consequences of organizational silence, ultimately leading to improved organizational effectiveness and performance.